2021
DOI: 10.3390/pharmaceutics13040568
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-Loaded Bioactive Coatings on Medical Grade Stainless Steel Promote Osteointegration

Abstract: In this study, a multilayer bioactive coating based on carboxymethyl cellulose (CMC) and dexamethasone (DEX) was prepared on medical-grade stainless steel (AISI 316LVM). Its aim was the controlled drug delivery of the incorporated anti‑inflammatory drug, which at the same time promotes osteogenic differentiation of mesenchymal stem cells. Due to DEX’s limited solubility in physiological fluids, which limits the loading capacity of coatings, it was further combined with β-cyclodextrin to increase its concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Specific staining revealed that the cells were positive for CD29, CD44, CD73, CD90, CD105 and CD166 and negative for CD14, CD31, CD34 and CD45 (adipose-derived mesenchymal stem cells; normal, human (ATCC PCS-500-011)). The cell line has been used to date for various research applications, including adipose tissue regeneration [ 21 ], osteointegration in bioactive coatings [ 22 ], chondrogenesis [ 23 ] and neurogenesis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific staining revealed that the cells were positive for CD29, CD44, CD73, CD90, CD105 and CD166 and negative for CD14, CD31, CD34 and CD45 (adipose-derived mesenchymal stem cells; normal, human (ATCC PCS-500-011)). The cell line has been used to date for various research applications, including adipose tissue regeneration [ 21 ], osteointegration in bioactive coatings [ 22 ], chondrogenesis [ 23 ] and neurogenesis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using ATR-FTIR, the bioactivity of prepared coatings was confirmed by signals related to PO 4 3 − , indicating apatite, in a study by De Santis et al [ 69 ] after ceria was combined with TNTs and soaked in SBF at 37 °C for 8 days. The technique can also offer information on whether the drug was successfully incorporated into the bioactive coatings and whether it was physically or chemically bound to the coatings [ 32 , 34 , 85 , 86 , 87 , 88 , 89 , 90 ]. In a study by Kiran et al [ 87 ], coatings of poly(ε-caprolactone) (PCL) nanofibers loaded with HA and rifampicin were electrospun on a Ti substrate.…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
“…Drugs for immunomodulation include dexamethasone ( Tejido-Rastrilla et al, 2018 ; Xu et al, 2019 ; Rozanc et al, 2021 ; Xiao et al, 2021 ), chondroitin sulfate ( Li Y.-M. et al, 2019 ), salidroside ( Yi et al, 2022 ), aspirin ( Wei et al, 2020 ) and so on. Among different antiinflammation drugs, dexamethasone can actually alleviate all levels of inflammation and is commonly used to treat various inflammatory diseases ( Rozanc et al, 2021 ). Xu et al ( Xu et al, 2019 ) developed a PDA-mediated dexamethasone plus minocycline-loaded liposomes on PEEK substrates.…”
Section: Pda-mediated Components For Multilayered Coatings On Biomate...mentioning
confidence: 99%